2016
DOI: 10.1016/j.susc.2015.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous carbon-supported Pd nanoparticles with high specific surface area for cyclohexene hydrogenation: Outstanding catalytic activity of NaOH-treated catalysts

Abstract: Extremely high specific surface area mesoporous carbon supported Pd nanoparticle catalysts were prepared with both impregnation and polyol-based sol methods. The silica template used for the synthesis of mesoporous carbon was removed by both NaOH and HF etching. Pd/mesoporous carbon catalysts synthesized with the impregnation method has as high specific surface area as 2250 m 2 /g. In case of NaOH etched impregnated samples, the turnover frequency of cyclohexene hydrogenation to cyclohexane at 313 K was obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…With having surface area (234 m 2 g ‐1 ) and total pore volume (0.13 cm 3 g ‐1 ), the HF etched OMC replica exhibited pronounced defective sites that bind or adsorbs ORR intermediates such as O*, OOH* or OH* by neither too weak nor too strong forces result in higher ORR activity . Puskas et al reported that the HF etched Pd doped porous carbons exhibit higher surface area (2400 m 2 g ‐1 ) compared to NaOH etched carbon samples (1400 m 2 g ‐1 ). In our case the NaOH etched mesoporous carbon shows low surface area and pore volume whereas, the PVDF etched carbon shows high surface area, however, the PVDF etched carbon exhibited high electrocatalytic activity is due to the more number of defective sites present in the material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With having surface area (234 m 2 g ‐1 ) and total pore volume (0.13 cm 3 g ‐1 ), the HF etched OMC replica exhibited pronounced defective sites that bind or adsorbs ORR intermediates such as O*, OOH* or OH* by neither too weak nor too strong forces result in higher ORR activity . Puskas et al reported that the HF etched Pd doped porous carbons exhibit higher surface area (2400 m 2 g ‐1 ) compared to NaOH etched carbon samples (1400 m 2 g ‐1 ). In our case the NaOH etched mesoporous carbon shows low surface area and pore volume whereas, the PVDF etched carbon shows high surface area, however, the PVDF etched carbon exhibited high electrocatalytic activity is due to the more number of defective sites present in the material.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the deconvoluted O1s peaks give three major peaks centered at 531, 532 and 534 eV belongs to the C‐O, C=O, C‐OH species, respectively . The HF and PVDF etched O1s peak shows high intensity and shifted around +2 eV (C=O) is confirms the presence of mesoporous carbon defective sites with some extent of graphitic nature,…”
Section: Resultsmentioning
confidence: 99%
“…In our case the observed variation in surface area and pore volume may due to the difference in various chemical process, ca., gas phase (PVDF) as well as liquid phase (HF, NaOH) etching methods employed. In a report by Puskas et al . the NaOH etching of Pd‐silica‐carbon composite showed only low specific surface area (1400 m 2 /g) when compared to HF etched material.…”
Section: Resultsmentioning
confidence: 99%
“…In order to compare the electrocatalytic activity of the as-prepared Pt/NG composites with that of a commercially used carbon black (CB, supplied by Cabot Corporation) support, a Pt/CB catalyst were prepared by the wet impregnation method as described elsewhere [41]. 90 mg of carbon black and 20 mg platinum(II)-acetylacetonate were suspended in 40 ml of distilled water.…”
Section: Preparation Of the Reference Catalystmentioning
confidence: 99%